Judicial Integrity: A Call for its Re-Emergence in the Adjudication of Criminal Cases - Bloom, Robert M. (1993)
A court can invalidate or rectify certain kinds of offensive official action on the grounds of judicial integrity. In the past, it has served as a check on overzealous law enforcement agents whose actions so seriously impaired due process principles that they shocked the bench’s conscience. The principle not only preserves the judiciary as a symbol of lawfulness and justice, but it also insulates the courts from becoming aligned with illegal actors and their bad acts. The 1992 case of U.S. v. Alvarez-Machain, however, may have signaled a departure from past practices. This article reviews current Supreme Court cases and finds that judicial integrity is no longer the bulwark it once was for justifying Fourth Amendment exclusionary remedies, sanctioning the Court’s use of supervisory powers, and the application of due process. The author contrasts the current Court’s view on judicial integrity with examples from Australia and New Zealand, where the doctrine has re-emerged and gained force. The author argues that in the United States, the pendulum has swung too far toward neglecting concerns inherent in the principles of judicial integrity and that judicial integrity needs to be restored